Strategi Pengelolaan Food Waste Berbasis Triple Bottom Line untuk Efisiensi Food Cost di Hotel X - Anastasia Amanda Ade Pambuyun; I Putu Arnawa; Ni Made Sri Rukmiyati (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the food waste management strategy implemented by Hotel X in an effort to streamline food costs and support sustainability. This study uses a qualitative descriptive approach by involving three key informants from hotel management. Data collection techniques are carried out through in-depth interviews, direct observations in the field, and documentation studies related to kitchen operational processes. Data analysis techniques are carried out based on the Miles & Huberman model which includes data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that Hotel X Bali implements a structured food waste management strategy, namely by planning the purchase of foodstuffs based on the occupancy rate of guests and paying attention to the expiration date using the First In First Out (FIFO) method. The hotel also uses a just-in-time system in the procurement of raw materials to avoid waste and stock buildup. Flexible menu planning strategies and employee training on food waste management also contribute to achieving food cost efficiency. In addition, food waste that is still suitable for consumption is distributed through the food donation program, while other organic waste is processed into compost. The implementation of this strategy has proven effective in reducing the amount of food waste, increasing operational efficiency, and strengthening Hotel X's commitment to sustainability principles based on the Triple Bottom Line approach (economic, environmental, and social). This strategy not only supports corporate social responsibility, but also improves the image and competitiveness of hotels in the eyes of consumers who are increasingly concerned about environmental issues.